Optically active tetra-tert-butyl-P(5)-deltacyclene epimers: preparation, spectroscopy, dynamic equilibriums, H/D exchange, and transition-metal complex chemistry. - Rohwer, Lars; Höhn, Christine; Autschbach, Jochen; Bauer, Walter; Heinemann, Frank Wilhelm; Torrell, Sergi Huguet; Keller, Irene; Shubina, Tatyana; Steffen, Jacob; Zenneck, Ulrich (Chemistry - A European Journal, 2014)
On the basis of isolated diastereomeric triorganylstannyl-P5 -deltacyclenes 7' and 7'', almost pure enantiomers of their destannylation products 8' and 8'' are now available. These stereochemically inert cage chiral species contain a configurationally labile P1H1 group that defines two epimers 8 a and 8 b of each of the enantiomers, which are connected by a rapid equilibrium. Mirror-symmetric circular dichroism (CD) spectra of the enantiomeric cages are compatible with the identification of epimers. A simulation of the CD spectrum of the major epimer 8'a relates the cage chirality of the system to the observed chiroptical effects. Both cage epimers and two of the phosphorus cage atoms are active as ligands with respect to [M(CO)5 ] fragments of Cr, Mo, and W. Four almost isoenergetic regio- and stereoisomers of the resulting mononuclear complexes are formed for these metals, but only one of the isomers per metal crystallized in the case of the racemic series of the complexes. The enantiopure versions of cages and cage complexes, however, did not crystallize at all, a well-known phenomenon for chiral compounds. CD spectra of the optically active complex isomer mixtures are close to identical with the CD spectra of the related free cages and point again to the chiral cages as the dominant source of the CD effects of the complexes. [(Benzene)RuCl2 ] complexes of the cage ligand 8 behave totally differently. Only a single species 12=[(benzene)RuCl2 ⋅8 b] is formed in almost quantitative yield and the minor epimer 8 b plays the role of the ligand exclusively. The reaction works as well for the separated enantiomeric cage versions to yield the highly enriched enantiomers 12' and 12'' separately. An efficient kinetic resolution process was identified as the main reason for this finding. It is based on a high stereo- and regiochemical flexibility of the PC cage ligand that is capable of adjusting to the specific requirements of a suitable transition-metal complex fragment. Such ligand flexibility is regularly observed in metalloenzymes, but is a very rare case in classical and organometallic complex chemistry.